Perceived overall injustice and organizational deviance—Mediating effect of anger and moderating effect of moral disengagement - Qin, Ge; Zhang, Lihua (Frontiers in Psychology, 2022)
This study is dedicated to exploring the influence of perceived overall injustice on employee emotion and behavior. Based on fairness heuristic theory and cognitive appraisal theory of emotion, a model was developed to investigate the relationship between perceived overall injustice, anger and organizational deviance. In addition, the roles of moral disengagement in moderating anger—organizational deviance and perceived overall injustice—organizational deviance have been discussed. The data were collected from three Chinese manufacturing corporations with a total effective sample size of 264. Statistical results showed that there is a significant positive relationship between perceived overall injustice, anger and organizational deviance. The moderating effect of moral disengagement on the relationship between perceived overall injustice and organizational deviance is significant, while that on the relationship between anger and organizational deviance is insignificant. Implications and limitations have been discussed.